Alterity (otherness) in the last writings of Lévinas - Waldenfels, Bernhard; Hoyos Vásquez, Guillermo (Estudios de Filosofía, 1999)
Emmanuel Lévinas is one of the first critics of a totalitarianism of reason and a centralism of the subject. This does not mean that he discards reason, giving way to an irrationalism; nor does it mean the subject is sentenced to death; it is rather a change in the coordinates of traditional thought, which is questioned by the other, a fundamental topic of the present article and of Levinas’ thought as a whole.